The Role of Islamic Principles in EFL Teaching Strategies within the Merdeka Curriculum - Hasibuan, Kalayo; Yana, Lulu Dewi; Lisaini, Ouvi (MODELING: Jurnal Program Studi PGMI, 2024)
This study investigates the integration of Islamic principles into English as a Foreign Language (EFL) teaching strategies within the Merdeka Curriculum, a student-centered educational framework in Indonesia. Recognizing the global importance of English and the ethical foundation of Islamic values, the research explores how values such as honesty, discipline, and respect can enhance EFL teaching practices. Using a qualitative approach and case study design, data were collected through interviews, classroom observations, and literature review. The findings show that integrating Islamic principles with the Merdeka Curriculum fosters a balanced educational environment that prioritizes both academic success and character development. Strategies like reflective practices, collaborative learning, and ethical discussions were found to effectively incorporate these values into teaching, promoting student engagement and enhancing critical thinking, moral reasoning, and language skills.The study also highlights the flexibility of the Merdeka Curriculum in embedding moral considerations into teaching, preparing students for academic and personal challenges. The implications suggest the need for a values-based approach to language education, with recommendations for teacher training and development of materials reflecting both linguistic and ethical goals. Future research could examine the long-term impact on students' holistic development and explore broader applications in education.